Manual of digital libraries - Vol ll - Dhiman, Anil Kumar (Ess Ess, 2012)
Digital libraries are gaining popularity among library and information science professionals. This book describes the various facets of digital libraries in the present scenario. Contents include: Concept of Digital Libraries * Digital Libraries: Components and Services * Documents in Digital Libraries * Internet and Internet Resources * Cataloguing of Digital Resources: Metadata and Its Creation * Digital Preservation * Information Access in Digital Libraries * Copyrights and Intellectual Property Rights * Library Consortia * E-learning and Digital Libraries * Open Access and Institutional Repositories * Open Source Software